Answer:
i think the answer is a) 9/5
Answer:
![SA=234.8\ yd^2](https://tex.z-dn.net/?f=SA%3D234.8%5C%20yd%5E2)
Step-by-step explanation:
we know that
The surface area of the regular pyramid is equal to the area of the triangular base plus the area of its three triangular lateral faces
step 1
Find the area of the triangular base
we know that
The triangular base is an equilateral triangle
so
The area applying the law of sines is equal to
![A=\frac{1}{2}(14^2)sin(60^o)](https://tex.z-dn.net/?f=A%3D%5Cfrac%7B1%7D%7B2%7D%2814%5E2%29sin%2860%5Eo%29)
![A=\frac{1}{2}(196)\frac{\sqrt{3}}{2}](https://tex.z-dn.net/?f=A%3D%5Cfrac%7B1%7D%7B2%7D%28196%29%5Cfrac%7B%5Csqrt%7B3%7D%7D%7B2%7D)
step 2
Find the area of its three triangular lateral faces
![A=3[\frac{1}{2}bh]](https://tex.z-dn.net/?f=A%3D3%5B%5Cfrac%7B1%7D%7B2%7Dbh%5D)
we have
![b=14\ yd](https://tex.z-dn.net/?f=b%3D14%5C%20yd)
Find the height of triangles
Applying the Pythagorean Theorem
![10^2=(14/2)^2+h^2](https://tex.z-dn.net/?f=10%5E2%3D%2814%2F2%29%5E2%2Bh%5E2)
solve for h
![100=49+h^2](https://tex.z-dn.net/?f=100%3D49%2Bh%5E2)
![h^2=100-49](https://tex.z-dn.net/?f=h%5E2%3D100-49)
![h=\sqrt{51}\ yd](https://tex.z-dn.net/?f=h%3D%5Csqrt%7B51%7D%5C%20yd)
substitute
![A=149.97\ yd^2](https://tex.z-dn.net/?f=A%3D149.97%5C%20yd%5E2)
step 3
Find the surface area
Adds the areas
![SA=84.87+149.97=234.84\ yd^2](https://tex.z-dn.net/?f=SA%3D84.87%2B149.97%3D234.84%5C%20yd%5E2)
Round to the nearest tenth
![SA=234.8\ yd^2](https://tex.z-dn.net/?f=SA%3D234.8%5C%20yd%5E2)
Answer:
x^2 | y^25 |√187x
Step-by-step explanation:
First you simplify the equation then you factor 184 into its prime factors which is 184 = 23 • 23
To simplify a square root, we extract factors which are squares, i.e., factors that are raised to an even exponent. Factors which will be extracted are: 4 = 22 Factors which will remain inside the root are: 46 = 2 • 23 To complete this part of the simplification we take the square root of the factors which are to be extracted. We do this by dividing their exponents by 2: 2 = 2 At the end of this step the partly simplified SQRT looks like this: 2 • sqrt (46x5y50) Rules for simplifing variables which may be raised to a power: (1) variables with no exponent stay inside the radical (2) variables raised to power 1 or (-1) stay inside the radical (3) variables raised to an even exponent: Half the exponent taken out, nothing remains inside the radical. examples: (3.1) sqrt(x8)=x4 (3.2) sqrt(x-6)=x-3 (4) variables raised to an odd exponent which is >2 or <(-2) , examples: (4.1) sqrt(x5)=x2•sqrt(x) (4.2) sqrt(x-7)=x-3•sqrt(x-1) Applying these rules to our case we find out that SQRT(x5y50) = x2y25 • SQRT(x) sqrt (184x5y50) = 2 x2y25 • sqrt(46x)
pls brainlist